The Shoah and the neighbor: the Holocaust as a trauma of Western thought and Levinas's "post-traumatic" philosophy - Luksch, Jakub (International journal for philosophy of religion, 2025)
This article analyzes the Shoah as a traumatic rupture within the tradition of Western philosophical thought, arguing that the Holocaust necessitates a fundamental reorientation of ethics and subjectivity. Drawing on the phenomenological tradition, particularly the work of Emmanuel Lévinas, the text proposes a framework of "post-traumatic philosophy" that resists the totalizing tendencies of classical ontology. Lévinas's radical conception of ethical responsibility—centered on the asymmetrical relation to the Other and the imperative of substitutability—is presented as a necessary response to the dehumanization wrought by the Nazi regime. The article further situates Lévinas in relation to other thinkers such as Rosenzweig, Benjamin, and Husserl, who anticipated or responded to the philosophical crises that culminated in the Shoah. By examining the limitations of Enlightenment rationality and the inadequacy of traditional metaphysics in the face of genocide, the study calls for an ethical paradigm that prioritizes alterity, responsibility, and the irreducible dignity of the human being. The Shoah, as a catastrophic event beyond assimilation, thus becomes the impetus for a transformation in philosophical discourse—one that confronts the failure of reason and affirms the ethical primacy of the Other.